The Effect of Capital Punishment on Terrorism in Saudi Arabia - Alqahtani, Mohammed; D’Alessio, Stewart J.; Stolzenberg , Lisa (Recent Research Advances in Arts and Social Studies Vol. 3, 2023)
Numerous studies investigate the deterrent effect of capital punishment on homicide levels, but no published study conducted to date focuses explicitly on the impact of capital punishment on terrorist activity. In addition, no research evaluates the possible deterrent effect of a mass execution. This study examines the influence of the mass execution of 47 terrorists by the Saudi government, which took place on January 2, 2016, on the frequency of terrorist attacks originating from within Saudi Arabia. Using missile and drone attacks that were launched from outside of Saudi Arabia as a statistical control variable, results generated in an interrupted time-series analysis show that the mass execution decreased the frequency of within-country terrorist attacks by approximately two attacks per month. Results further reveal that the Saudi military intervention in Yemen amplified within-country terrorist activity by nearly five attacks per month. These findings suggest that the use of capital punishment may prove to be useful in deterring terrorist attacks.